Jail Library Service : A Guide for Librarians and Administrators - Bayley, Linda; Association of Specialized and Cooperative Library Agencies, Chicago, IL. (Washington, D.C. : Distributed by ERIC Clearinghouse, 1981)
Designed to provide basic information on joint planning of library services for jail populations by correctional and library personnel and inmates, this curriculum guide covers 10 topics: (1) a rationale for library services in jails; (2) the characteristics and role of the jail librarian; (3) the first steps in planning library services; (4) assessing the needs of inmates; (5) options for the delivery of jail library service and record keeping; (6) types and sources of materials and working with a materials selection policy; (7) service options, i.e., literacy programs, GED or high school completion, learner's advisory service, college-level examination program, correspondence courses, reentry classes or seminars, programs on topics of special interest, legal referral service, and information and referral; (8) how to develop community support for the jail library programs; (9) sources of funding, including suggestions for writing proposals; and (10) how to evaluate the program. Sample checklists, worksheets, and questionnaires are included, as well as short written exercises for the user of the guide. Appended materials include a list of national resources, library standards for jails and detention centers, a sample materials selection policy, sample policy statements, and sample questionnaires for interest surveys. (SD)
Administrators.
Media Staff.
Community.
Practitioners.
Microfiche.
Keywords: Cooperative Planning; Correctional Institutions; Instructional Materials; Guides, Non-Classroom.; Tests/Questionnaires.